#TITLE_ALTERNATIVE# - ARYA (NIM: 10113035), EMMANUEL
In the field of life insurance and pension, calculating reserves is a necessity to anticipate unexpected insurance policy claims in the future. Calculating insurance reserves consider the risk of the policyholder’s death (which is modeled in the disability model) and the risk of the policy expiry (which is modeled in the behavioral model). The combination of those models will form a new model called the ’combination model’. Modeling those mathematical models can be done by using the Markov chain approach. The advantage of using this approach is the Markov chain’s ability to consider more than one state for each model. By using Markov chain model, the calculation of insurance reserves is expected to be more accurate. Some cases regarding the policy and disability status will be in sight, so the impact to reserves calculation can be observed.